Biological activities and chemical constituents of Chromolaena odorata (L.) King & Robinson / Faridah Hj Jasnie - Haji Jasnie, Farnidah (2009)
Chloromolaena odorata was screened for its phytochemical properties and pharmacological activities. Phytochemical screening of C. odorata indicates the presence of terpenoid, flavonoid and alkaloid. GCMS analysis of the leaf extract of C. odorata shows four major compounds which are cyclohexane, germacrene, hexadecoic acid and caryophyllene. While, HPLC analysis has identify five peaks; quercetin-4 methyl ether, aromadendrin-4’-methyl ether, taxifolin-7-methyl ether, taxifolin-4’-methyl ether and quercetin-7-methyl ether, kaempferol-4’-methyl ether and eridicytol-7, 4’-dimehyl ether, quercetin-7,4’-dimethyl ether. By using the column chromatography, three compounds were isolated; 5,7-dihydroxy-2-(4-methoxyphenyl)chromen-4-one; 3,5-dihydroxy-2-(3-hydroxy-4-methoxy-phenyl)-7-methoxy-chromen-4-one and of 2-(3,4-dimethoxyphenyl)-3,5-dihydroxy-7-methoxy-chromen-4-one. The toxicity evaluation and dermal irritation of the aqueous leaf extract of C. odorata verifies that it is non-toxic at the maximum dose of 2000mg/kg. For the formaldehyde induced paw oedema evaluation, it proves that the leaf extract of the plant is 80.24% (concentration of 100mg/kg) as effective as Indomethacine (standard drug). The methanolic extract (100mg/ml) of the plant shows negative anti- coagulant, as it causes blood clot in less than two minutes. Meanwhile, the petroleum ether and chloroform leaf extract shows negative anti-coagulant, as they prolong the blood coagulation from to two minutes to more than three minutes. For the result of anti-microbial evaluation, C. odorata shows medium inhibition on S. aureus ATCC 25293, weak inhibition on S. aureus ATCC 29213 and strong inhibition on P. aeruginosa but no inhibition on the fungi, C. albicans. The last evaluation which is wound healing evaluation certifies the rapid wound healing to four days (concentration of 300mg/kg) only from six days (using acriflavine lotion).